Thermodynamics and Modeling of Sorption Isotherms. Issue 3 (10th February 2016) - Adolphs, Jürgen
Abstract: An extended version of the thermodynamic computation model for sorption isotherms and capillary condensation is introduced. With the combination of the excess surface work (ESW) and disjoining pressure approach sorption isotherms for various pore size distributions of cylindrical and slit‐like mesopores are successfully modeled. The main idea is that during adsorption on pore walls the approaching films will collapse and capillary condensation proceeds, while evaporation is described with a modified Kelvin equation. In both cases adsorption and desorption, the surface tension dependency on the pore size is considered. Abstract : Combining the thermodynamic approaches excess surface work and disjoining pressure allows the successful modeling of sorption isotherms including hysteresis effects. Capillary condensation is described with the collapse of adsorbed films, while an extended Kelvin equation is applied for desorption. In all cases, the pore size effect on the surface tension is considered.